2019
DOI: 10.1021/acs.molpharmaceut.8b01123
|View full text |Cite
|
Sign up to set email alerts
|

Cell Permeable NBD Peptide-Modified Liposomes by Hyaluronic Acid Coating for the Synergistic Targeted Therapy of Metastatic Inflammatory Breast Cancer

Abstract: Chronic inflammation is closely related to the development, deterioration, and metastasis of tumors. Recently, many studies have shown that down-regulating the expression of inflammation by blocking nuclear factor-κB (NF-κB) and signal transducer and activator of transcription 3 (STAT3) pathways could significantly inhibit tumor growth and metastasis. The combined application of curcumin (CUR) and celecoxib (CXB) has been proven to exert a synergistic antitumor effect via inhibiting the activation of NF-κB and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 36 publications
1
33
0
Order By: Relevance
“…Therefore, the favorable effect of the NBD peptide is not only due to the inhibition of proinflammatory NF-κB signaling, but also through the restoration of redox balance. Our findings in the context of diabetes-induced kidney disease are consistent with other studies emphasizing the powerful therapeutic effects of different NBD-based strategies in preclinical models of Duchenne muscular dystrophy [28], Parkinson's disease [50], arthritis [27], breast cancer [31] and ischemic acute kidney injury [51]. A recent phase I trial of NBD peptide administration in dogs with large B-cell lymphoma demonstrated safety and efficacy [32], offering hope for translation to human disease.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Therefore, the favorable effect of the NBD peptide is not only due to the inhibition of proinflammatory NF-κB signaling, but also through the restoration of redox balance. Our findings in the context of diabetes-induced kidney disease are consistent with other studies emphasizing the powerful therapeutic effects of different NBD-based strategies in preclinical models of Duchenne muscular dystrophy [28], Parkinson's disease [50], arthritis [27], breast cancer [31] and ischemic acute kidney injury [51]. A recent phase I trial of NBD peptide administration in dogs with large B-cell lymphoma demonstrated safety and efficacy [32], offering hope for translation to human disease.…”
Section: Discussionsupporting
confidence: 87%
“…Studies have identified a specific region in the C-terminal of IKKα (L738-L743) and IKKβ (L737-L742) that is essential for adequate assembly of the IKKα/β-NEMO complex, accordingly named the NEMO-binding domain (NBD) [26,27]. Based on this region, several cell-permeable NBD peptides have been characterized, thus providing an opportunity to selectively abrogate proinflammatory NF-κB activity in preclinical experimental models of inflammatory diseases [27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…21 In vitro Cellular Uptake and Cytotoxicity Figure 4A illustrated that the cellular uptake of HA-I/ D-LPNs was higher than I/D-LPNs (P < 0.05), which may be the evidence that HA-I/D-LPNs have CD44-targeting effect. 41 In vitro cytotoxicity results showed that HA-I/ D-LPNs exhibited remarkable better cell inhibition . HA modified LPNs showed slower drug/ gene release than that of unmodified LPNs.…”
Section: In Vitro Drug and Gene Releasementioning
confidence: 97%
“…Additionally, knockdown of PTPN2 leads to EGF-mediated STAT3 activation [22]. The association of chronic inflammation with breast cancer progression is widely recognized, but it can be inhibited by blocking STAT3 [23]. Other mediators of STAT3 signaling pathways are also extensively studied.…”
Section: Advances In the Study Of Stat3 Signaling Pathways In Breast mentioning
confidence: 99%